Autobiographical Elements in Sons and Lovers - Mukherjee, Arnab (Integrated Journal for Research in Arts and Humanities, 2023)
Lawrence had begun writing the novel Sons and Lovers as a tribute to his mother. The plot is firmly knit and the characters are well drawn. It contains some of Lawrence’s finest descriptions of life in the mining village. The first title given to it was ‘Paul Morel’. The novel is autobiographical, Paul Morel being Lawrence himself. However, whatever we receive in this novel is not pure autobiography but autobiography fictionalized. So, it is an adaptation from life and a work of art. Majority of the critics call this novel as ‘semi autobiographical’. Analyzing all the important events in the novel this article tries to find out all the autobiographical elements present in it by exploring the lives of all the major characters in the novel as well as of those real persons on whose life they are modeled on.